Bagaimana Fenomena ‘Marriage is Scary’ dalam Pandangan Perempuan Generasi Z? - Lestari, Melina; Aimma, Sandhian Lasti; Cahyadi, Shafa Fajriandini; Putri, Khaila Alfiory Lestari Legowo; Mustofa, Mona Maimun (UPT Publikasi dan Pengelolaan Jurnal Universitas Islam Kalimantan MAB Banjarmasin, 2024)
This research aims to examine the views of Generation Z women regarding the